Shifting Conversations on Online Distance Education in South Korean Society During the COVID-19 Pandemic: A Topic Modeling Analysis of News Articles - Lee, Kyungmee; Kim, Tae-Jong; Cefa Sari, Berrin; Bozkurt, Aras (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2023)
This study explored the dominant discourses on online distance education (ODE) that emerged in South Korean society before, during, and after the COVID-19 pandemic. The authors conducted a topic modeling analysis of 8,865 news articles published by 24 South Korean media outlets between 2019 and 2021. Using the Latent Dirichlet Allocation (LDA) algorithm and social network analysis software (NetMiner), the top five topics and the top ten words associated with each topic were identified from each period. The authors observed significant changes not only in the number of news articles but also in the depth of the conversations published each year. The results have revealed several key points. First, ODE, previously considered marginal and abnormal, gained in normality across all educational levels in Korean society. Second, ODE discourses have been shaped by the unique cultural, historical, and technological infrastructure in South Korea. Third, a clear division between social-justice-oriented and business-oriented ODE discourses reflect a persistent inequality in Korean society. Finally, ODE discourses matured in 2021, with more critical and realistic perspectives on both the positives and negatives of ODE. The useful implications of such insights for post-pandemic ODE research and practice are further discussed.